2018
DOI: 10.1177/0748233717753780
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of the genotoxicity of CeO2 nanoparticles in human peripheral blood lymphocytes using cytokinesis-block micronucleus test, comet assay, and gamma H2AX

Abstract: Engineered nanoparticles (ENPs) are used in a wide range of applications because of their unique properties. Cerium dioxide nanoparticles (CeO NPs) are one of the important ENPs, and they can cause negative health effects, such as genotoxicity, in humans and other living organisms. The aim of this work was to analyze the genotoxic effects of short-term (3-24 h) CeO NPs exposure to cultured human blood lymphocytes. Three genotoxicity systems "cytokinesis-block micronucleus test, comet assay, and gamma H2AX test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 43 publications
2
11
0
1
Order By: Relevance
“…Previous studies generally demonstrated that doses higher than those employed in the present study, i.e., 40, 80 or even 200 µg/mL depending on the cell type, are required to observe genotoxic effects evaluated by the comet assay on cell lines exposed to these NPs [ 33 , 39 , 46 ]. However, similarly to our findings, Auffan et al [ 47 ] and Könen-Adıgüzel and Ergene [ 48 ] obtained dose-dependent increases of DNA damage at very low doses of CeO 2 NPs employing human dermal fibroblasts and peripheral blood leucocytes, respectively, treated in vitro. With regard to the oxidative DNA damage, the positive responses observed in the current experiments for the three tested NPs are in agreement with previous studies employing FPG- or hOGG1-modified comet assays for evaluating TiO 2 NPs [ 17 , 49 , 50 ], ZnO NPs [ 16 , 19 ], and CeO 2 NPs [ 49 ].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies generally demonstrated that doses higher than those employed in the present study, i.e., 40, 80 or even 200 µg/mL depending on the cell type, are required to observe genotoxic effects evaluated by the comet assay on cell lines exposed to these NPs [ 33 , 39 , 46 ]. However, similarly to our findings, Auffan et al [ 47 ] and Könen-Adıgüzel and Ergene [ 48 ] obtained dose-dependent increases of DNA damage at very low doses of CeO 2 NPs employing human dermal fibroblasts and peripheral blood leucocytes, respectively, treated in vitro. With regard to the oxidative DNA damage, the positive responses observed in the current experiments for the three tested NPs are in agreement with previous studies employing FPG- or hOGG1-modified comet assays for evaluating TiO 2 NPs [ 17 , 49 , 50 ], ZnO NPs [ 16 , 19 ], and CeO 2 NPs [ 49 ].…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, the genotoxic effect of CONPs (<25 nm) was investigated on human lymphocyte cultures at concentrations range of 6, 12, and 18 mg/mL. It was reported that DNA damage occurred in the H2AX and Comet tests at 3 h and in the MN method at 24 h. There was no significant difference between concentrations when dose-related genotoxicity was evaluated, and the genotoxicity increased significantly at 72 h of exposure in all used tests (Könen-Adıgüzel and Ergene, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, several reports suggested that the uptake of nanoceria could induce oxidative stress and DNA damage, apoptosis, dephosphorylation of various substrates, aberrant cell signaling, and alterations in the transcriptional and posttranslational levels. 3,[30][31][32] Biomedical Relevance of Nanoceria Kailashiya, Dash…”
Section: Toxicity and Adverse Effectsmentioning
confidence: 99%